1991
DOI: 10.1002/lsm.1900110302
|View full text |Cite
|
Sign up to set email alerts
|

Presence of human immunodeficiency virus DNA in laser smoke

Abstract: Concentrated tissue culture pellets infected with human immunodeficiency virus (HIV) containing 1 x 10(7) cells/ml were vaporized by means of a carbon dioxide laser. The vaporous debris resulting from the laser's impact were evacuated through sterile silastic tubing, then bubbled through sterile culture medium (RPMI) positioned in series with a commercial smoke evacuator. No HIV DNA was detected in the culture medium flask. Tissue culture studies of the silastic collection tubing revealed p24 HIV gag antigen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
125
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(126 citation statements)
references
References 7 publications
0
125
0
Order By: Relevance
“…More worrying is the in vitro isolation of human immunodeficiency virus (HIV), although it could not be cultured beyond 14 days, possibly due to thermal damage. 12 However, there is currently no evidence that infections have been transmitted to humans in this way, except anecdotal reports of nasopharyngeal infection in surgeons treating papillomas. 7,15 The occurrence of port-site metastases following laparoscopic bowel cancer resections led to concerns that surgical smoke carried malignant cells, deposited as the pneumoperitoneum escapes around the trocar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More worrying is the in vitro isolation of human immunodeficiency virus (HIV), although it could not be cultured beyond 14 days, possibly due to thermal damage. 12 However, there is currently no evidence that infections have been transmitted to humans in this way, except anecdotal reports of nasopharyngeal infection in surgeons treating papillomas. 7,15 The occurrence of port-site metastases following laparoscopic bowel cancer resections led to concerns that surgical smoke carried malignant cells, deposited as the pneumoperitoneum escapes around the trocar.…”
Section: Discussionmentioning
confidence: 99%
“…11 Lung damage was prevented by filtering the smoke. 12 A major concern is the risk of transmission of biological agents. Ferenczy et al 13 demonstrated the presence of potentially infectious human papilloma virus (HPV) DNA, but not intact viruses, but were unable to isolate any DNA or virus from samples taken from the surgeon during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…During laser resurfacing, Corynebacterium and Neisseria were cultured from laser smoke (Capizzi, Clay, & Battey, 1998). Human immunodeficiency virus-1 (HIV-1) has been identified in surgical smoke (Johnson & Robinson, 1991), and HIV DNA has been detected in smoke for 14 days after extraction (Baggish, Poiesz, Joret, Williamson, & Refai, 1991) but has not been grown in tissue cultures (Johnson & Robinson, 1991). Similarly, some studies have identified human papillomavirus (HPV) in surgical smoke (Garden et al, 1988;Kashima, Kessis, Mounts, & Shah, 1991;Sawchuk, Weber, Lowy, & Dzubow, 1989) but others have not (Abramson, DiLorenzo, & Steinberg, 1990).…”
Section: Research On the Hazardous Nature Of Surgical Smokementioning
confidence: 99%
“…Human immunodeficiency virus (HIV) proviral DNA, and intact viral DNA from the human papilloma virus have been found in plume produced by lasers. 8,9 Other biological material collected from surgical smoke include intact and fragmented human cells and intact DNA. 10,11 In addition to biological material, chemical byproducts have also been found in the surgical smoke, including various volatile organic compounds, polycyclic aromatic compounds, aldehydes, cresols, phenol, hydrogen cyanide, and carbon monoxide.…”
Section: Surgical Smokementioning
confidence: 99%